2016
DOI: 10.11124/jbisrir-2016-003170
|View full text |Cite
|
Sign up to set email alerts
|

Nursing clinical handover improvement practices among acute inpatients in a tertiary hospital in Sydney: a best practice implementation project

Abstract: The findings showed how audits may be used to promote best practice in healthcare and that focused education and provision of relevant resources can have an immediate and positive impact on clinical practice. Some of the measured criteria improved to a moderate degree, leaving room for improvement; however, by the end of the project attitudes toward nursing clinical handover had been "transformed" from a passive routine "must do" task to an active process with a focus on safety and patient/carer engagement. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 10 publications
3
30
0
1
Order By: Relevance
“…Other studies found that following various handover interventions, including the implementation of standardized handover tools (Jukkala et al, 2012) and moving the handover location to patient bedside (Mcallen et al, 2018), nurses reported increased accuracy of information exchanged and more effective handover communication (Jukkala et al, 2012; Mcallen et al, 2018). Furthermore, Wainwright and Wright (2016) conducted a project with the aim to increase nurses' compliance with handover best practice across 11 units in a large tertiary hospital. An education bundle consisting of video and written materials, as well as face‐to‐face educations sessions, was implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found that following various handover interventions, including the implementation of standardized handover tools (Jukkala et al, 2012) and moving the handover location to patient bedside (Mcallen et al, 2018), nurses reported increased accuracy of information exchanged and more effective handover communication (Jukkala et al, 2012; Mcallen et al, 2018). Furthermore, Wainwright and Wright (2016) conducted a project with the aim to increase nurses' compliance with handover best practice across 11 units in a large tertiary hospital. An education bundle consisting of video and written materials, as well as face‐to‐face educations sessions, was implemented.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of this project comprised baseline and follow‐up postimplementation nursing clinical handover observational audits measured against seven best practice recommendations. The results of this project demonstrated significant improvements in the nurses’ compliance with best practice criteria (Wainwright & Wright, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered essential for continuity of patient care. [5] Even though there was a form of verbal handover occurring, shift leaders reported that many times information was missing from the previous shift. Much of their time was spent trying to retrieve that information.…”
Section: Context and Settingmentioning
confidence: 99%
“…If, however, they do not have a system of letting the oncoming shift know this information, vital patient data is missed and errors occur. [1,5] With the goal to reach the needs of the patients by 2020, the Ministry of Health in Rwanda launched a program called Human Resources for Health (HRH) to train nurses, doctors, and dentists in the latest standards of care. [6] Part of achieving these goals included training the nurses in A/E to focus on proper communication during handover report so that patients could receive optimal streamlined care.…”
Section: Introductionmentioning
confidence: 99%
“…Effective communication during the shift‐to‐shift nursing handover has been the focus of international research for many years, as the accuracy of information transferred can directly impact patient safety (Halm, 2013; Wainwright & Wright, 2016).…”
Section: Introductionmentioning
confidence: 99%